Expression of TGF, matrix metalloproteinases, and tissue inhibitors in Chinese chronic rhinosinusitis - Li, Xiaoyuan; Meng, Juan; Qiao, Xiaoming; Liu, Yafeng; Liu, Feng; Zhang, Nan; Zhang, Jie; Holtappels, Gabriele; Luo, Ba; Zhou, Peng; Zheng, Yongbo; Lin, Ping; et al. (Journal of allergy and clinical immunology, 2010)
To date there is no information on the expression of mediators associated with tissue remodeling in Asian patients with chronic rhinitis with (CRSwNP) or without (CRSsNP) nasal polyps. To study the expression of TGF-β1, matrix metalloproteinases (MMPs), tissue inhibitors of metalloproteinases (TIMPs), collagen, and regulatory T cells in Chinese patients with CRSwNP and CRSsNP. Thirty-six male and female subjects (12 patients with CRSwNP, 12 patients with CRSsNP, and 12 control subjects), age 17 to 60 years, were recruited into the study. Samples were collected from polyp and sinusoidal mucosal, ethmoidal mucosal, or inferior turbinate in the respective groups and assessed for TGF- β1, MMP-2, MMP-7, MMP-9, TIMP-1, TIMP-2, TIMP-3, and TIMP-4 by immunoassay; collagen by histochemistry; and forkhead box P3 (FOXP3) mRNA by real-time PCR. Patients with CRSwNP showed significantly lower concentrations of TGF-β1, TIMP-1, TIMP-4, FOXP3, and collagen compared with patients with CRSsNP. Although there were no significant differences between the concentrations of MMP-7 and MMP-9 in patients with CRSwNP and CRSsNP, these were significantly increased compared with control patients. MMP-2 and TIMP-2 concentrations were not significantly different in any patient group, whereas TIMP-3 was not detectable. Chronic rhinosinusitis with nasal polyps is characterized by a relative lack of TGF-ß expression versus CRSsNP. This finding may be causal for decreased collagen, TIMP-1/4, and FOXP3 expression in CRSwNP versus CRSsNP. TGF-ß serves as a main switch for different remodeling patterns in sinus disease.